Looking at the best: A detailed analysis of elite race walking technique - Salvage, J.; Seaman, T. (Walking Promotions, 2009)
Looking at the Best, A detailed analysis of elite race walking technique takes the discussion of race walking locomotion further than ever before. By combining high resolution - high speed photography with computer software and detailed measurements, we paint an image of exactly how the best race walkers in the world stride forward at speeds approaching 10 mph (16 kph). Instead of theorizing the body motions comprising ideal race walking technique, we analyze the race walkers from elite race walk competitions featuring the very best race walkers in the world. Under race conditions (primarily at the 12th World Championships in Berlin), we see the good, bad and ugly with regard to technique. By using real race photographs we take the discussion out of the proverbial laboratory and examine how race walkers do what we want to do, race fast.